2008
DOI: 10.1111/j.1529-8027.2008.00177.x
|View full text |Cite
|
Sign up to set email alerts
|

Small Rho GTPases are key regulators of peripheral nerve biology in health and disease

Abstract: A thorough knowledge of the cellular and molecular basis of the structure and function of peripheral nerves is of paramount importance not only for a better understanding of the fascinating biology of the peripheral nervous system but also for providing critical insights into the various diseases affecting peripheral nerves as the firm foundation of potential treatments. Genetic approaches in model organisms, in combination with research on hereditary forms of neuropathies, have contributed significantly to ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 127 publications
0
6
0
Order By: Relevance
“…They displayed Schwann cells (Benninger et al, 2007). In addition, Cdc42 may be required for membrane wrapping and transition from promyelinating to myelinating Schwann cells (Krause et al, 2008). In support of this idea, disruption of frabin/FGD4, a GTPase exchange factor that regulates Cdc42 activity (Umikawa et al, 1999), causes demyelinating Charcot-Marie-Tooth (CMT4H) neuropathy (Delague et al, 2007;Stendel et al, 2007).…”
Section: Impaired Motor Activity In Mutant Mice Lacking N-wasp In Myementioning
confidence: 96%
See 3 more Smart Citations
“…They displayed Schwann cells (Benninger et al, 2007). In addition, Cdc42 may be required for membrane wrapping and transition from promyelinating to myelinating Schwann cells (Krause et al, 2008). In support of this idea, disruption of frabin/FGD4, a GTPase exchange factor that regulates Cdc42 activity (Umikawa et al, 1999), causes demyelinating Charcot-Marie-Tooth (CMT4H) neuropathy (Delague et al, 2007;Stendel et al, 2007).…”
Section: Impaired Motor Activity In Mutant Mice Lacking N-wasp In Myementioning
confidence: 96%
“…3 D). Interestingly, inducible deletion of Cdc42 in Schwann cells (Krause et al, 2008) indicated that it is important for the transition from the promyelinating to the myelinating stage during remyelination, making it likely to regulate this process through N-WASP. Given that Cdc42 is activated by neuregulin (Benninger et al, 2007), N-WASP could provide a direct imperative link between ErbB2/3 receptor signaling and actin rearrangement during myelination.…”
Section: N-wasp Is Required For Schwann Cell Membrane Wrapping and Myelinationmentioning
confidence: 99%
See 2 more Smart Citations
“…The experiments performed here, which detected changes in total cellular Rho GTPase activity, were not designed to detect subcellular changes in activation of Rac1 or RhoA, which also may be important. In Schwann cells, the ability of Rac1 to regulate lamellipodia formation and process extension is linked to its effects on myelination and axonal sorting (15,46,47).…”
Section: Discussionmentioning
confidence: 99%